Parent‐Mediated Online Reading intervention for children with Down Syndrome. Issue 2 (17th June 2019) - Grindle, Corinna; Tyler, Emily; Murray, Clodagh; Hastings, Richard P.; Lovell, Michael
Abstract : Evidence suggests that reading interventions found to be effective with typically developing children may also be effective with children with developmental disabilities (DD). The Headsprout® Early Reading programme (HER) is an online reading programme accessible at home or at school. Previous research using HER with children with DD has been delivered by trained staff in special school contexts. However, access to trained staff is limited, and many children with DD do not attend special schools. These factors may limit the number of children able to benefit from a potentially effective intervention. Training and involving parents to support their child's reading may increase the number of children who might benefit, and also reflects current education policy. We examined the feasibility of using HER with five children with Down Syndrome in a six‐month parent mediated intervention. Standardised tests of reading ability carried out pre‐post intervention, showed that skills with phoneme segmentation improved following HER, and word reading age improved on average 13 months (range 6 to 20 months). These data are promising and support a rationale for larger evaluation studies.